(untitled) (International Journal of Built Environment and Sustainability, 2022)
The morphological patterns of the Malay town are analysed using three main elements of urban form: road networks, building plots, and open space. However, considering the physical aspects of a city, as well as the impact of geography, social, economic, and political forces, allows us to establish a city’s particular character, which may be altered by multiple socioeconomic changes brought on by the pandemic. There are few well-documented systematic procedures for examining the morphological changes associated with Malay settlement features, implying considerable differences in the approaches used. By describing techniques and analysing the urban form, this article aims to spark discussion on what an antifragile built environment might look like. It also aims to shed light on how to create dynamic pseudo adaptability in the old and historic town, particularly in terms of scale, urban morphology, and social life, by establishing a systematic analytical framework for the analysis of urban morphology. To exemplify the process of building the methodological structure, a single case study was undertaken in Kota Bharu’s Old Settlement Zone. The case study is subdivided into four sections: a) conceptual structure, b) case study design framework, and c) mapping research framework. It is defined through an iterative process that described the specifics of crucial features to establish an extensive methodological framework for the Malay settlement by thoroughly developing and scrutinising methodological processes. Because the current pandemic is sharpening our understanding of the link between local and global action, as well as the power inherent in the application of professional and technical knowledge and practice, this paper hoped to help with the development of policies and guidelines, as well as the evaluation of proposals for post-pandemic urban morphological assessments.